1986
DOI: 10.2527/jas1986.631176x
|View full text |Cite
|
Sign up to set email alerts
|

Age, Dose of FSH and Other Factors Affecting Superovulation in Holstein Cows

Abstract: Effects of age of donor and other factors on superovulation and production of transferable embryos were investigated. Data were obtained on 987 recoveries of embryos performed between November 1980 and June 1984 by Select Embryos, Inc. The 339 Holstein donors ranged in age from 1.8 to 17.8 yr. The effects of age of donor and dose of follicle stimulating hormone (FSH) were examined using regression analysis. For on-farm recoveries, numbers of embryos, rates of fertilization, quality scores of all embryos and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0
6

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(62 citation statements)
references
References 23 publications
7
49
0
6
Order By: Relevance
“…According to Looney (1986), in a study conducted on 2048 donor cows, 70% of the embryos were collected from only 30% of the donors. Similar variability was reported for a group of more than 900 dairy cows (Lerner et al 1986). …”
Section: Introductionsupporting
confidence: 84%
“…According to Looney (1986), in a study conducted on 2048 donor cows, 70% of the embryos were collected from only 30% of the donors. Similar variability was reported for a group of more than 900 dairy cows (Lerner et al 1986). …”
Section: Introductionsupporting
confidence: 84%
“…Mean values of donor parity, milk production and postparturient day after ER were not statistically different among the groups. Increasing parity did not affect ERs or TEs as in previous studies [9,12,22], even though a large-scale parity analysis could not be done in Korea. Milk yield was not related to the production of TEs.…”
Section: Discussionmentioning
confidence: 47%
“…Moreover, the season when ER was conducted in this study had no significant effect on the production of TEs, but other studies of the effect of season on the superovulatory response of cattle have yielded conflicting results. While some researchers [15,22] have reported an influence of season on superovulatory response, others [25,28] did not find a consistent effect of season on ovarian response. Therefore, it is suggested that the conventional parameters did not influence the superovulatory response and that they could not be used as indicators of donor selection in Korean Holstein cattle.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A study conducted by Lerner et al (1986) with 339 Holstein donors reported that the increased donor age reduces the number of recovered structures and viable embryos. An alternative proposed by these authors to change this situation would be to increase the FSH dose, but this increase did not have the same result in heifers.…”
Section: Resultsmentioning
confidence: 99%